Decision Support System Against Customer Management Loyalty in Silvi Using SAW Method - Fifit Alfiah; Dita Setiawan; Ade Setiadi (Universitas Raharja, 2023)
Online financial institutions or currently often referred to as Finance Technology (Fintech) are one of the institutions that are developing in the digital and IoT era with official support from OJK. One of them is PT. Kreigan Sentral Teknologi which has the Silvi application for mobile or android users, the system currently running on the Silvi application still has several problems such as errors in calculating the number of customer transactions carried out by management which are still semi-computerized using Microsoft Excel where management spends considerable time time to calculate customer loyalty data. Therefore, to increase customer loyalty in the Silvi application, this research aims to make customers more comfortable and interested in making transactions using the Silvi application where for each customer transaction, the company will provide loyalty in the form of a Silvi balance reward supported by a design customer loyalty management decision support system using the method SAW (Simple Additive Weighting) to make it faster and more effective in calculating the number of customer transactions so that customers are more interested in making transactions. The results of this study are that the system is able to make decisions in determining customer loyalty carried out by company management in processing customer transaction calculations with a 90% success percentage in determining customer loyalty in the Silvi application.